Economics, Business and Management (EBM): Theoretical Logic, Practical Value, and Future Paths - Ganyongxiang Ganyongxiang (Journal of International Conference Proceedings, 2025)
Against the backdrop of the deep integration of the digital economy and the real economy, Economics, Business and Management (EBM)—as an interdisciplinary system integrating multi-disciplinary theories and practical tools—has become a core support for solving complex business decision-making problems and promoting high-quality economic development. This study aimed to systematically clarify EBM’s theoretical connotation, logical framework, practical effects, and development dilemmas. The research adopted literature review, case study, and empirical analysis methods: literature review sorted EBM’s theoretical evolution; case study analyzed 3 typical enterprise applications; empirical analysis used panel data of 32 manufacturing enterprises (2021-2024) to test EBM’s effect. Results showed EBM-oriented management reduced production costs by 7.5%-12.3% and increased total factor productivity by 8.9% on average, with the Epsilon-Based Measure model being 15.7% more accurate than traditional DEA models in environmental efficiency evaluation. Conclusions indicate EBM’s interdisciplinary value, while practical dilemmas like disciplinary barriers require optimization via interdisciplinary integration and digital empowerment. The study enriches interdisciplinary management theory and provides practical references for enterprises’ sustainable development.